A note on some integrals involving two associated Laguerre polynomials - Shawagfeh, Nabil (Rev. Téc. Fac. Ing. Univ. Zulia)
A cl0sed form expresslon In terms ofAppells function F2 is derived for the integral oftwo Associated Laguerre polynomials of the form 00 fe-uxA-t L (ax)L ( x)dx O Sorne Integral formulas correspondlng to special values of the parameters and the arguments are deduced. the results are belleved to be new.